2012
DOI: 10.1029/2012jd017630
|View full text |Cite
|
Sign up to set email alerts
|

A parametrization, based on sea ice morphology, of the neutral atmospheric drag coefficients for weather prediction and climate models

Abstract: Abstract.A hierarchy of parametrizations of the neutral 10 m drag coefficients over polar sea ice with different morphology regimes is derived on the basis of a partitioning concept that splits the total surface drag into contributions of skin drag and form drag. The new derivation, which provides drag coefficients as a function of sea ice concentration and characteristic length scales of roughness elements, needs fewer assumptions than previous similar approaches. It is shown that form drag variability can ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
236
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(241 citation statements)
references
References 40 publications
3
236
2
Order By: Relevance
“…stand-alone atmosphere or coupled ocean-sea-ice-atmosphere model). Compared to pre-IPY results, the role of melt ponds in the parameterizations by Andreas et al (2010) and Lüpkes et al (2012a) is a new aspect. Lüpkes et al (2013) showed on the basis of sea ice concentration and melt pond fraction data obtained by MODIS (Rösel et al, 2012) that the inclusion of the melt pond effect on roughness has a significant impact on the drag coefficients to be used in climate models.…”
Section: Surface Roughness and Momentum Fluxmentioning
confidence: 76%
See 2 more Smart Citations
“…stand-alone atmosphere or coupled ocean-sea-ice-atmosphere model). Compared to pre-IPY results, the role of melt ponds in the parameterizations by Andreas et al (2010) and Lüpkes et al (2012a) is a new aspect. Lüpkes et al (2013) showed on the basis of sea ice concentration and melt pond fraction data obtained by MODIS (Rösel et al, 2012) that the inclusion of the melt pond effect on roughness has a significant impact on the drag coefficients to be used in climate models.…”
Section: Surface Roughness and Momentum Fluxmentioning
confidence: 76%
“…In addition to the skin friction over smooth ice/snow surface, the aerodynamic roughness of sea ice is affected by factors generating form drag: ridges, floe edges, and sastrugi (Andreas et al, 2010a, b;Andreas, 2011;Lüpkes et al, 2012aLüpkes et al, , 2013. This generates a challenge for operational modelling: the above-mentioned characteristics of sea ice surface vary rapidly in time and often over small spatial scales, but they are difficult to observe by remote sensing.…”
Section: Surface Roughness and Momentum Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Tremblay and Mysak, 1997;Hopkins, 2004;Schreyer et al, 2006;Wilchinsky and Feltham, 2006;Sulsky et al, 2007;Girard et al, 2011;Tsamados et al, 2013;Herman, 2016;Rabatel et al, 2015;Dansereau et al, 2016), and wind and/or ocean drag parameterisations (e.g. Lu et al, 2011;Lüpkes et al, 2012;Tsamados et al, 2014). These developments still need to be further evaluated regarding their contribution to better reproduce the complexity of sea ice dynamics mentioned earlier, in realistic set-ups.…”
Section: P Rampal Et Al: Nextsim: a New Lagrangian Sea Ice Modelmentioning
confidence: 99%
“…Wave-ice interaction fractures the ice and leads to smaller floes in the marginal ice zone. The average floe size typically varies with the ice concentration and was parametrized in the marginal ice zone by Lüpkes et al [42] to be:…”
Section: I) Prognostic Mixed Layer Model In the Arcticmentioning
confidence: 99%